MULTIPLICATION COUNTING TRAINING USING JARIMATIKA FOR THE CHILDREN IN GAMPONG SEUBON KEUTAPANG LHOKNGA ACEH BESAR - Nazariah, Nazariah; Yani, Muhammad; Karina, Nadila (ABDIMU: Jurnal Pengabdian Muhammadiyah, 2021)
Community service about counting training using Jarimatika can make children more interesting in counting, so that mathematics in everyday life is very fun. There are several activities, namely the planning, implementation, and evaluation stages of learning. In contrast to the theory of mathematics learning steps in elementary schools, there is only the implementation of learning and there is no planning and evaluation of learning. However, in the theory of multiplication counting steps using the Jarimatika method, the Application of the Jarimatika Method in Multiplication LearningKey words: Multiplication, Jarimatika, Seubon Keutapang